Heterometallic Coordination Polymers Based on Cuii/Lniii Cations. Solid-State and Magnetic Characterization - Venegas-Yazigi, D; Venegas-Yazigi, D (Academic Press, 2021)
Novel heterometallic three-dimensional coordination polymers {[CuII2LnIIICl2(HIA)4(NO3)(DMF)2]∙(2DMF)∙(H2O)}n based on Ce (1), Eu (2) or Gd (3) and imidazole-4-acrylic acid (H2IA), were successfully synthesized using the sonochemical method. All attempts to obtain the compound using other synthetic methods were unsuccessful. The heterometallic polymers are isostructural, crystallizing in the chiral P3221 trigonal space group. The crystal structures correspond to an intricated 3D framework where the Cu(HIA)2 fragments generate two interpenetrated copper (II) networks, [Cu(HIA)2]n. The LnIII cations that interact with these CuII-networks through the carboxylate group belonging to the organic ligand confer a higher complexity to the 3D network. Additionally, the coordination environment around the copper (II) cations is responsible for the chirality of the structures, making these even more exciting. The three-dimensional polymers were also characterized from a magnetic point of view, obtaining for (1) and (2) antiferromagnetic interactions, while for (3) a ferromagnetic interaction was observed. Furthermore, to the best of our knowledge, these coordination polymers are the first heterometallic compounds based on 3d/4f cations, assembled by the ligand imidazole-4-acrylate (HIA−). © 2021 Elsevier Inc.